Quantitative Measurement of Retained Oil in Organic-Rich Shale—A Case Study on the Chang 7 Member in the Ordos Basin, China - Hou, Lianhua; Luo, Xia; Lin, Senhu; Zhao, Zhongying; Li, Yong (Frontiers in Earth Science, 2021)
This study proposes a method to calculate the retained oil content (WO) in cores collected by a sealed tool from organic-rich shale with thermal maturity around%Ro = 0.8 in the Ordos Basin, China. Approaches such as soaking cores at low temperature, multiple extractions, multiple pyrolysis, and multiple chromatographic analyses were conducted and then the relationships between total retained oil content and mineral compositions were analyzed. The total retained oil content measured by the method proposed in this paper is 60–260% higher than that measured by a conventional pyrolysis method and 34–69% higher than the sum (WO) of two extractions with dichloromethane (WO3) and chloroform (WO4). After extractions with dichloromethane and chloroform (WO5), the oil retained in the organic-rich shale was 4.7–11.6%, which has not been extracted. Positive correlations exist between WO (i.e., WO3 + WO4) and total organic carbon (TOC) and S1 (absorbed hydrocarbon by rock pyrolysis), and WO has the highest correlation coefficient with the former. The method can provide important guidance for the objective analysis of retained oil in organic-rich shale, and it is reliable for the evaluation of shale oil reserves.